Global Declining Competition - Diez, Federico (IMF Working Papers; Working Paper, 2019)
Using a new firm-level dataset on private and listed firms from 20 countries, we document five stylized facts on market power in global markets. First, competition has declined around the world, measured as a moderate increase in average firm markups during 2000- 2015. Second, the markup increase is driven by already high-markup firms (top decile of the markup distribution) that charge increasing markups. Third, markups increased mostly among advanced economies but not in emerging markets. Fourth, there is a non-monotonic relation between firm size and markups that is first decreasing and then increasing. Finally, the increase is mostly driven by increases within incumbents and also by market share reallocation towards high-markup entrants.